STRUKTUR KOMUNITAS TUMBUHAN PAKU (PTERIDOPHYTA) DI KAWASAN HUTAN KUSU-KUSU KECAMATAN NUSANIWE DAN SOYA KECAMATAN SIRIMAU KOTA AMBON SEBAGAI SUMBANGAN ILMIAH BAGI MATA KULIAH EKOLOGI TUMBUHAN - Jeanne L Maalalu; Dominggus Rumahlatu (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: Nail plants (Pteridophyta) are cormus plants whose bodies can be clearly distinguished between roots, stems, and leaves. However, ferns cannot produce seeds because they breed with spores. Nail plants are divided into 4 classes, namely (1) Psilophytinae (ancient nail); (2) Lycopodiinae (wire nail); (3) Equisetinae (horsetail); and (4) Filicinae (true nail). Community structure is a concept that studies species composition or composition and its abundance in a community. Method: This research is a quantitative descriptive study to reveal information about the community structure of ferns. The study was conducted on July 18, 2018 - August 18, 2018. Results: The ferns found in the Kusu-Kusu forest area were 10 species and the Soya region as many as 20 species. Overall the types of ferns found in the two study locations were grouped into 2 classes, namely Filicinae / Pteropsida (true nail) and Lycopodiinae (wire nails). The Filicinae / Pteropsida class has a greater number of species, both in the Kusu-Kusu forest area (8 species) and the Soya forest area (13 species). The Lycopodiinae class has a smaller number of species, both in the Kusu-Kusu forest area (2 types), and the Soya forest area (7 species). Conclusions: 10 ferns were found in the Kusu-Kusu Sereh forest area in Nusaniwe Subdistrict, while in the Soya District of Sirimau District there were 20 species.